Written tests as a learning assessment strategy in the Optometry career - Aburto Garcés, Fabrina Anyelit (2023)
The objective of this study is to analyze the use of written tests as a learning evaluation strategy in students of the Medical Optometry career. The methodological approach is mixed, for which were designed quantitative and qualitative instruments such as surveys, interviews and documentary review. The following analytical categories were identified: Types of reactive or items present in the written tests, level of learning achieved, planning process for the preparation of the written tests and student perception. Most of the teachers use multiple-choice reagents in the written tests. In the process of preparing the written tests, the teachers carry out a bibliographic search, review of the lesson plans and the subject program; however, they do not create a table of specifications or distribution of reagents, nor do they establish evaluation criteria or achievement indicators. The conceptual, procedural and attitudinal contents evaluated in the tests written by the teachers of the different subjects agree with those declared in the subject syllabi. The students state that the content of the exams is related to the topic developed in class.